Mobile Money, Entrepreneurship and Labor Dynamics in Developing Countries - Moussavi, Arman. (Tufts University. Tisch Library., 2022)
Thesis (M.S.)--Tufts University, 2022.; Submitted to the Dept. of Economics.; Advisor: Alan Finkelstein Shapiro.; Keyword: Economics.